Sexual risk nehaviour of street Youth in South West Nigeria (2009)
Objectives Previous studies have mainly focused on sexual behaviour of in-school Nigerian youths with little attention to those on the street. This survey was conducted to determine the sexual risk behaviours of young people on the streets of Ibadan, Nigeria. Methodology A cross sectional survey was conducted among youths aged 15-24 years in the major markets, motor parks and commercial areas in two local government areas in Ibadan. Participants in the study areas were identified in groups based on their occupational activity and all consenting young people were interviewed. A semi-structured questionnaire was used to obtain information on sexual behaviours, condom use and history of sexually transmitted infections. Data was managed using SPSS version 11. Results Most (68.8%) were males, 79.0%, were sexually experienced, the median age at sexual debut for males was 15 years and 16 years for females. More females (53.9%) compared to (34.5%) males reported that their first partners were five or more years older, p<0.01. Condom use during the first sexual intercourse was reported by only 32.2%. Sex with a commercial sex worker or exchange of sex for money was reported by 18.2% (20.6% of males versus 12.2% of females, p=0.01). Factors significantly associated with history of transactional sex were; male gender; older age (20-24 years); being out of school and regular alcohol use. Multiple sexual partnering was reported by 58.2%, the significant predictors were male gender; early age at sexual debut; regular alcohol use and history of transactional sex. Inconsistent condom use was reported by 44.8%, the predictors were female gender; regular alcohol use and history of transactional sex in the previous year. Conclusion Majority of these young people on the streets are sexually active and many engage in high risk sexual behaviours. Development of appropriate sexual and reproductive health interventions is recommended.